2020
DOI: 10.1016/j.applthermaleng.2020.115999
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical characteristics and application of metallic-oxide based mono and hybrid nanocomposite phase change materials for thermal management systems

Abstract: This experimental study covers the chemical, physical, thermal characterization and application of novel nanocomposite phase change materials (NCPCMs) dispersed by TiO 2 , Al 2 O 3 , and CuO nanoparticles. A commercial-grade of paraffin, namely RT-35HC, was considered as a phase change material (PCM). The mono and hybrid NCPCMs were synthesized at a constant weight concentration of 1.0 wt.%. In the first phase, various characterization techniques were used to explore the thermophysical properties and chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…The maximum and minimum increment of decomposition temperatures are about 4.38% and 0.166%, respectively, among the different nanocomposite PCMs. The improvement in thermal stability of the nanocomposite PCM is due to the improvement in specific heat capacity and improved TC, as both enhance the uniform heat distribution in the PCM 25,35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum and minimum increment of decomposition temperatures are about 4.38% and 0.166%, respectively, among the different nanocomposite PCMs. The improvement in thermal stability of the nanocomposite PCM is due to the improvement in specific heat capacity and improved TC, as both enhance the uniform heat distribution in the PCM 25,35 …”
Section: Resultsmentioning
confidence: 99%
“…Santosh et al 23 compared surface roughened PCM and Al 2 O 3 nano‐dispersed PCM by analyzing their thermal performance and presented their results. The thermophysical characteristics of nanocomposites with mono and hybrid nanoparticles were studied by Arshad et al 24,25 They reported that the developed hybrid nanocomposite PCMs had improved thermal properties and can be used for thermal management of electronic devices. Selimefendigil and Sirin 26 experimentally investigated a parabolic greenhouse dryer using nano‐enhanced PCM.…”
Section: Introductionmentioning
confidence: 99%
“…This problem must be overcome to guarantee operation at low temperature but for a very long period compared to that guaranteed by addition of single nanoparticles. For this, the addition of hybrid nanoparticles has shown the ability of NePCM to lower the electronic component working temperature and clearly extend the latent heat phase duration where the electronic component operates away from any risk or failure 34 . The hybrid nanoparticles fraction has a significant influence since NePCM with 1%‐Al 2 O 3 and 3%‐Cu has decreased the temperature further compared to that with 2%‐Al 2 O 3 and 2%‐Cu.…”
Section: Resultsmentioning
confidence: 99%
“…So, it requires encapsulation of PCM. This weakness of material depending on its nature can be improved using different methods investigating by researchers including increasing the heat transfer area (Aydin et al, 2018), geometric optimization (Yazici et al, 2014), dispersing particles (Arshad et al, 2020), metal matrix (Alhusseny et al, 2020), impregnated graphite foam/matrix (Py et al, 2001), encapsulation (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%